2010
DOI: 10.1021/jp101695s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Atmospheric Gases on the Electrical Properties of PbSe Quantum-Dot Films

Abstract: We report the effects of N2 and O2 on the electrical properties of PbSe quantum-dot (QD) films treated with 1,2-ethanedithiol (EDT) by measuring the changes in the current−voltage characteristics of QD field-effect transistors (FETs). EDT-treated PbSe QD films at a base pressure of ∼10−5 Torr exhibit ambipolar transport. Exposing these films to N2 shifts the transfer characteristics toward negative gate-voltage values and increases the electron mobility. These changes could be reversed entirely by removing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(117 citation statements)
references
References 39 publications
(92 reference statements)
4
113
0
Order By: Relevance
“…Previous reports showed that BDT ligand exchanged PbSe fi lms are unstable when devices are exposed to ambient conditions. [ 34,72,73 ] Hence, the heterogeneity in ligand exchange reactions can lead to a distribution in surface sites, and these can be additional sources of midgap energy states.…”
Section: Synthesis Characterization and Stability Of Pbse Ncsmentioning
confidence: 99%
“…Previous reports showed that BDT ligand exchanged PbSe fi lms are unstable when devices are exposed to ambient conditions. [ 34,72,73 ] Hence, the heterogeneity in ligand exchange reactions can lead to a distribution in surface sites, and these can be additional sources of midgap energy states.…”
Section: Synthesis Characterization and Stability Of Pbse Ncsmentioning
confidence: 99%
“…In order to absorb visible light and generate electron-hole pairs, ZnO nanorods should be coupled to a narrow band gap sensitizing material. Early researchers have used organic dye molecules and inorganic quantum dots for visible sensitization in ZnO nanorod array electrodes for solar cell applications [3]. CdS has the same crystal structure as that of ZnO, its band gap (2.4 eV) is in the visible region and it can be synthesized by a simple and inexpensive chemical bath technique.…”
Section: Introductionmentioning
confidence: 99%
“…For both EDT and oxalic acid, the effective mobility of the samples with the Al 2 O 3 film was consistently higher than that for TFT without encapsulation by approximately two orders of magnitude. This could be due to different degrees of oxidation in the PbSe nanocrystal films [16], [17], [21], [28]. Although not clearly understood, two competing oxidation mechanisms have been previously identified for these materials [16], [17], [21].…”
Section: Resultsmentioning
confidence: 98%
“…Major improvements to the charge mobility of PbSe nanocrystal films have been reported using either short-chain dithiols or hydrazine for ligand exchange [2], [15]. However, these molecules introduce undesirable instability against oxidation upon exposure to air, degrading the electrical and optical properties of the films [16], [17]. Specifically, PbSe nanocrystal films capped with carboxylic acid functional groups have been shown to improve oxidation resistance while maintaining favorable mobility and conductivity, but the stability against oxidation is still limited only to short-term exposure to air [18], [19].…”
Section: Introductionmentioning
confidence: 99%